Identifying factors influencing COVID-19 vaccine uptake in Finland – a qualitative study using social media data - Lohiniva, Anna-Leena; Pensola, Annika; Hyökki, Suvi; Sivelä, Jonas; Härmä, Vuokko; Tammi, Tuukka (Frontiers in Public Health, 2023)
Vaccine demand creation requires understanding what is driving the uptake of the vaccine. Qualitative research methods are paramount to gaining a localized understanding of behavioral drivers and barriers to vaccine uptake, but they are often underutilized. This is a qualitative study that used public comments on the Facebook and Twitter posts of the Finnish Institute for Health and Welfare (THL) as data sources to identify behavioral drivers for COVID-19 vaccine uptake in Finland. The participatory data analysis utilized thematic analysis and the Theoretical Domains Framework (TDF). NVIVO was used to assist in the coding process. The greatest number of FB and Twitter comments were linked with six TDF domains: knowledge, environmental context and resources, beliefs in consequences, beliefs in capabilities, social and professional role, and social influences. The domains included 15 themes that were interlinked. The knowledge domain overlapped with all other domains. By using public discourse on Facebook and Twitter, and rapid qualitative data analysis methods within a behavioral insight framework, this study adds to the emerging knowledge about behavioral drivers of COVID-19 vaccines that can be used by public health experts to enhance the uptake of vaccines during future pandemics and epidemics.